WHATSAPP SEBAGAI MEDIA DAKWAH PENYULUH AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN BACA TULIS AL-QUR’AN - Wawan Setiawan; Rizky Putri Amalia; Vina Vionita (Institut Nahdlatul Ulama Tasikmalaya, 2023)
Indonesia is the largest Muslim country in the world, therefore it has a special attachment that occurs with the Koran. As it is known that the Koran is the foundation of life for Muslims and cannot be separated from their lives throughout the world. So that in this case learning to read and write the Koran will continue to experience development and become a demand for educators and students to study it properly. This condition is no exception for the women of the taklim assembly, who are in the Al-Ihsan taklim assembly, Cibugel sub-district. One of the educators at the institution is an Islamic religious instructor. Since the emergence of the covid-19 virus, the recitation process has been carried out online via Whatsapp. The method used in this study is descriptive qualitative with a phenomenological approach and a constructivist paradigm. The results of this study indicate that the da'wah method used by Islamic religious instructors in conveying their da'wah to improve Al-Qur'an literacy through WhatsApp at the Al-Ihsan taklim assembly is by oral dakwah, namely conveying da'wah along with Al-Ihsan reading and writing guidance. the Qur'an directly orally or in writing sent to the WhatsApp group which consists of all members of the Al-Ihsan Taklim Assembly via the voice note feature or WhatsApp text message. The selection of WhatsApp media was considered by the ability to use the media of the women of the Al-Ihsan Taklim Assembly who generally have the application, they consider the use of WhatsApp media to be the easiest compared to other media. The features in the whatsapp media are also functional considering that the program aims to improve Al-Qur'an reading and writing skills, religious instructors utilize the voice note feature to send Al-Qur'an readings and image features to send Al-Qur'an writings and the congregation of the Al-Ihsan taklim assembly. Then in the process there are supporting factors, namely the existence of internal factors within the congregation of the taklim assembly, a high desire to learn as well as enthusiasm to continue carrying out recitation activities even though online through WhatsApp media even though at this time face-to-face recitations can be carried out again. While the inhibiting factor is the existence of internal factors that cause difficulties in learning to read and write the Qur'an, namely the feeling of laziness and shame that exists within the congregation.